Polyribosome Isolation in the Presence of Diethyl Pyrocarbonate - Weeks, Donald P. (1969)
Isolation of polyribosomes from wheat embryos and corn root tips in the presence of diethyl pyrocarbonate showed this reagent to have a protective effect on polyribosome structure. In addition, the use of diethyl pyrocarbonate allowed initial homogenization to be performed under less stringent conditions than those normally employed for polyribosome isolation. The use of the reagent is however limited, in that it is deleterious to in vitro ribosomal amino acid incorporation.